2021
DOI: 10.1080/20008198.2021.1882781
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and rates of PTSD, depression and anxiety in UK frontline health and social care workers during COVID-19

Abstract: Background: Studies have shown that working in frontline healthcare roles during epidemics and pandemics was associated with PTSD, depression, anxiety, and other mental health disorders. Objectives: The objectives of this study were to identify demographic, work-related and other predictors for clinically significant PTSD, depression, and anxiety during the COVID-19 pandemic in UK frontline health and social care workers (HSCWs), and to compare rates of distress across different groups of HCSWs working in diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
123
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(138 citation statements)
references
References 40 publications
12
123
0
3
Order By: Relevance
“…This made it particularly difficult for staff who were redeployed during the pandemic, who did not always feel included in their new ingroup but were no longer part of their old ingroup and could be left without clear lines of management support. Other quantitative research [ 3 ] has shown that being redeployed was a significant risk factor for health and social care workers developing PTSD in the context of the pandemic. Additional psychosocial support for redeployed staff is therefore likely to be of paramount importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This made it particularly difficult for staff who were redeployed during the pandemic, who did not always feel included in their new ingroup but were no longer part of their old ingroup and could be left without clear lines of management support. Other quantitative research [ 3 ] has shown that being redeployed was a significant risk factor for health and social care workers developing PTSD in the context of the pandemic. Additional psychosocial support for redeployed staff is therefore likely to be of paramount importance.…”
Section: Discussionmentioning
confidence: 99%
“…Early quantitative research emerging from the UK [ 2 4 ] and around the world [ 5 , 6 ] has demonstrated a significant mental health burden experienced by frontline workers in response to COVID-19, with elevated rates of depression, anxiety, post-traumatic stress disorder (PTSD) and suicidality reported. In the UK, it has been estimated that 45–58% of the frontline health and social care workforce met criteria for clinically significant levels of anxiety, depression and/or PTSD shortly following the first wave of the pandemic [ 2 , 3 ]. This is amongst a workforce already under considerable strain pre-COVID-19, as evidenced by the growing incidence of stress, burnout, depression, drug and alcohol dependence and suicide across all groups of health professionals, worldwide [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Together, these are likely to produce a sharp increase in a wide range of mental health problems, not limited to the most widely studied symptoms of anxiety and depression (e.g. Alexandra Maftei & Holman, 2021 ; Allan et al, 2020 ; Bareeqa et al, 2020 ; BinDhim et al, 2021 ; Cénat et al, 2021 ; de Pablo et al, 2020 ; Ertan, El-Hage, Thierree, Javelot, & Hingray, 2020 ; Greene et al, 2021 ; Shi et al, 2020 ; Vindegaard & Benros, 2020 ; Wu et al, 2021 ; Xiong et al, 2020 ). Identifying the various mental health consequences of the COVID-19 pandemic is a priority but still frequently neglected or minimized in national and international intervention plans (Brewin, DePierro, Pirard, Vazquez, & Williams, 2020 ).…”
mentioning
confidence: 99%
“…Nothing less could be found among the healthcare workers who are dealing with the COVID-19 patients (Allan et al, 2020). For example, in survey of UK doctors in May 2020, 45% reported experiencing depression, anxiety, stress, burnout or other mental health problems during the pandemic (Green et al, 2021).…”
Section: Discussionmentioning
confidence: 99%